Ferramenta para criação de clusters virtuais para o ensino de programação paralela e distribuída - Maia, Régis Matheus Silveira (2016)
In colleges and universities, teaching the concepts of parallel and distributed computing information technology students (IT) has become an increasingly important issue. To practice these concepts need an environment where those conducting the trial in real execution environment, which in the case of parallel and distributed computing is not always facial access. In this sense, this work aims to create a tool for parallel programming teaching and distributed in colleges and universities, so that students can practice the concepts learned in the classroom in a virtual and similar to the real environment where the student can create your own virtual cluster, to practice the concepts. To validate the developed tool was created a case study where a performance analysis was done, where we analyzed the time of creation of virtual clusters in developed tool.